LEGAL PERSPECTIVES ON FOREST PROTECTION WITHIN NATURAL RESOURCE LAW: CHALLENGES AND SOLUTIONS IN THE MINING SECTOR - Irawan, Loveleen Shaquiela (Communale Journal, 2025)
This study explores forest protection from the perspective of natural resource law, focusing on the challenges and solutions related to mining activities in Indonesia. Forest areas in Indonesia are under severe threat due to the expansion of extractive industries, particularly mining, which often operates within or adjacent to forest zones. The study identifies three major areas of concern: legal conflicts and institutional overlap in forest governance, weak enforcement of environmental laws and accountability mechanisms, and the marginalization of local communities in decision-making processes. The research reveals that inconsistencies between forestry, environmental, and mining regulations contribute significantly to forest degradation. Furthermore, the lack of coordination among government institutions, insufficient environmental monitoring, and the failure to uphold indigenous and community rights exacerbate the problem. Through a legal and socio-environmental lens, the study proposes integrated governance reforms, strengthened law enforcement, and increased community participation as essential solutions to ensure sustainable forest management. These findings underscore the importance of aligning legal frameworks with environmental justice and sustainable development principles to safeguard Indonesia’s forest ecosystems from the adverse impacts of mining.